On practising in physical education: outline for a pedagogical model - Aggerholm, K.; Standal, O.; Barker, D. M.; Larsson, H. (Physical education and sport pedagogy, 2018)
Background: Models-based approaches to physical education have in recent years developed as a way for teachers and students to concentrate on a manageable number of learning objectives, and align pedagogical approaches with learning subject matter and context. This paper draws on Hannah Arendt's account of vita activa to map existing approaches to physical education as oriented towards: (a) health and exercise, (b) sport and games, and (c) experience and exploration. Purpose: The aim of the paper is to outline a new pedagogical model for physical education: a practising model. We argue that the form of human activity related to practising is not well represented in existing orientations and models. To sustain this argument, we highlight the most central aspects of practising, and at the same time describe central features of the model. Relevance and implications: The paper addresses pedagogical implications the practising model has for physical education teachers. Central learning outcomes and teaching strategies related to four essential and 'non-negotiable' features of the practising model are discussed. These strategies are: (1) acknowledging subjectivity and providing meaningful challenges, (2) focusing on content and the aims of practising, (3) specifying and negotiating standards of excellence and (4) providing adequate time to practising. Conclusion: The practising model has the potential to inform new perspectives on pedagogical approaches, and renew and improve working methods and learning practices, in physical education.